The Influence of Pre-Marriage Class on Knowledge of Bride and Groom in Prevention of Stunting Toddlers - Sumardilah, Dewi Sri; Astuti, Retno Puji; Aprina, Aprina (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
The direct causes of stunting under five are inadequate food consumption and infectious diseases. The two direct causal factors are closely related to the quality of parenting. Efforts to handle stunting toddlers must be carried out as early as possible, not only since the mother is pregnant but must be carried out since the mother is still a prospective bride. In this context, it is necessary to find a model for the development of training for prospective brides that is in accordance with the needs in preventing stunting under five and seeing its effectiveness. This study will use a combination of descriptive observational design and quasi-experimental design. The research population is prospective brides in Kemiling District, and the sample is determined by accident, namely prospective brides who have registered at KUA Kemiling District until July 2021. Data collection for the development of pre-wedding classes is carried out by means of FGD and interviews, while to assess the effect of class pre-marriage used a quasi-experimental design with pre and post-test approaches. The analysis was carried out descriptively (frequency distribution) to determine the pre-marital class and bivariate analysis (dependent and independent test) to determine the effect of pre-marital class on the knowledge of the prospective bride and groom in preventing stunting under five. The results showed that the standard competencies needed by prospective brides to prevent stunting under five were exclusive breastfeeding, complementary feeding, balanced nutrition, monitoring of toddler growth, infectious diseases in children, pregnancy, and reproductive health. In the case group that was given treatment in the form of leaflets and premarital classes, there was an increase in knowledge scores between 78.9% to 125.6%, while in the control group which was only given leaflets the increase in knowledge scores only rose by 25.9% to 91.6 %. The results of the dependent test showed that there was a significant difference in knowledge scores between before and after treatment. Meanwhile, the results of the independent test showed that there was a significant difference in knowledge scores on exclusive breastfeeding (p=0.000), complementary feeding (p=0.019), child growth monitoring (p=0.002), pregnancy (p=0.001), and reproductive health (p=0.001). = 0.020) between the two groups.